P300-mediated acetylation increased the protein stability of HIPK2 and enhanced its tumor suppressor function. Issue 1 (December 2017) - Choi, Jong-Ryoul; Lee, Seo-Young; Shin, Ki; Choi, Cheol; Kang, Shin
Abstract Homeodomain-interacting protein kinase 2 (HIPK2) is a nuclear serine/threonine kinase that functions in development and tumor suppression. One of the prominent features of this kinase is that it is tightly regulated by proteasomal degradation. In the present study, we present evidence suggesting that the protein stability of HIPK2 can be regulated by p300-mediated acetylation. p300 increased the protein level of HIPK2 via its acetyltransferase activity. p300 increased the acetylation of HIPK2 while decreased polyubiquitination and its proteasomal degradation. We also observed that DNA damage induced acetylation of HIPK2 along with an increase in the protein amount, which was inhibited by p300 RNAi. Importantly, p300 promoted p53 activation and the HIPK2-mediated suppression of cell proliferation, suggesting acetylation-induced HIPK2 stabilization contributed to the enhanced activation of HIPK2. Overexpression of p300 promoted the HIPK2-mediated suppression of tumor growth in mouse xenograft model as well. Taken together, our data suggest that p300-mediated acetylation of HIPK2 increases the protein stability of HIPK2 and enhances its tumor suppressor function.